(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Today English has become the global common ground for communication. It’s the language of business, education, science, and even pop culture. No matter where you are in the globe, speaking English opens up a world of opportunities for business, personal growth, and building strong relationships. This article explores the importance of English in today’s world, highlighting its significance in international communication, education, technology, business, and cultural exchange. As a dominant language in the digital age, English enables individuals to access a wealth of information, engage with diverse perspectives, and navigate the complexities of a globalized world. Proficiency in English empowers individuals to connect with others, seize opportunities, and participate in a interconnected global community.